PERANCANGAN SISTEM INFORMASI ARUS KAS PADA PT. SUKSES ABADI ENGINEERING MENGGUNAKAN APLIKASI VISUAL STUDIO - Bokings, T. P. O Riska; Vathaprasit, Suon (Unit Penelitian dan Pengabdian kepada Masyarakat Politeknik TEDC Bandung Jl. Pesantren Km 2 Cibabat Cimahi Utara, Cimahi 40513 Jawa Barat, Indonesia, 2023)
This final project aims to record cash flow reporting procedures and design a cash flow information system at PT. Sukses Abadi Engineering using visual studio application. The research method uses descriptive methods with a qualitative approach and the data collection techniques used are library studies, documentation techniques, question techniques and observation techniques. The type of data used is a qualitative approach and the data sources obtained are passive primary data and internal secondary data. This final project uses the SDLC (System Development Life Cycle) method with the waterfall model as system development, programming language using visual studio applications, using Microsoft SQL Server as a database, system testing using Black Box and Crystal Reports used for making cash flow reports. This system consists of two (2) levels of access, namely admin and user. This cash flow information system is expected to help PT. Sukses Abadi Engineering in processing data related to cash in and cash out.